Exposure to electromagnetic field, cell phone use behaviors, SAR values, and changes in health following exposure in adolescent university students - İkinci keleş, Ayşe; Uzun Şahin, Ceyda (Arquivos de Neuro-Psiquiatria, 2021)
Background: The use of technological devices is growing rapidly, and the use of cell phones increases in parallel. Dependence on technological devices is a particular factor in this increased exposure. Many studies have been performed on this electromagnetic field, but no definite conclusions have been drawn. Objective: The purpose of this research was to investigate exposure to electromagnetic field, cell phone use behaviors, the specific absorption rate (SAR) values, and changes in health occurring after exposure in university students. Methods: A questionnaire was administered to 1,019 volunteer students aged 18–24 years at the Niğde Ömer Halisdemir and Recep Tayip Erdoğan Universities in 2018–2019. The questions were based on a survey of the literature. Results: The students spent an average 4–8 hours per day on their cell phones, and findings such as headache (p=0.002), concentration deficit (p=0.001), tiredness on waking in the morning (p=0.001), hyperactivity (p=0.001), general feeling of fatigue (p=0.001), and lethargy (p=0.001) increased in a statistically significant manner with length of use. Conclusions: Participants exhibited high levels of cell phone use and experienced biological, behavioral, and sleep problems. They also had very little knowledge about specific SAR values, an important criterion concerning cell phones.
Keywords: Adolescent; Surveys and Questionnaires; Cell Phone; Electromagnetic Field; Absorption